The silence of memory : Armistice Day 1919 - 1946 - Gregory, Adrian 1994- (The legacy of the Great War, 1994)
This book examines how the British people came to terms with the massive trauma of the First World War. Although the literary memory of the war has often been discussed, little has been written on the public ceremonies on and around 11 November which dominated the public memory of the war in the inter-war years. This book aims to remedy the deficiency by showing the preeminence of Armistice Day, both in reflecting what people felt about the war and in shaping their memories of it